Design of Lean Manufacturing to Improve Efficiency of The Coffee Agro-Industry Supply Chain - Sriwana, Iphov Kumala; Santosa, Budi; Pambudi, Hardian Kokoh; Maulanisa, Nida Fariza (Universitas Al Azhar Indonesia, 2025)
nappropriate material processing and supplying activities in a coffee agro-industry supply chain potentially lead to excessive waste, resulting in very low efficiency. Efficiency in the coffee agro-industry supply chain has to be considered, since the coffee agro-industry provides relatively high contribution to GDP, approximately 13.7%. Wasteful activities may significantly affect the GDP earned if not being eliminated. This study was aimed to identify waste produced along the coffee agro-industry supply chain and provide recommendations for improving supply chain efficiency, from the harvesting to the ground coffee processing. Actors of the coffee agro-industry supply chain consist of various parties, i.e. farmers, collectors, processors, and consumers. The supply chain is comprised of internal, external, and overall activities in which material and information flows are integrated within business units that traverse simultaneously between direct suppliers and consumers. In order to achieve optimum results, efficiency improvement by eliminating all sources of waste must be carried out at each stage. The method used to obtain this efficiency was Lean manufacturing, initiated with identifying waste using Process Activity Mapping (PAM), followed by identification with Current Value Stream Mapping (VSM). The efficiency value of the current condition was 93,9%. This shows the condition is good and there is no waste in time. There are other waste that needs to be analyzed, namely motion analysis and process. Keywords - Coffee, Efficiency, Supply Chain, Process Activity Mapping, Value Stream Mapping.